Peran Akuntansi Biaya untuk Mengurangi Risiko Keuangan pada Usaha Perikanan Tradisional di Pesisir - James Pelupessy (P3M Politeknik Negeri Ambon, 2024)
This research aims to explore cost accounting practices in the scope of fishing businesses. Coastal communities and traditional fishing businesses in coastal areas are often faced with high financial risks that affect business sustainability. This research method uses a descriptive qualitative approach. Data was collected mainly through direct interviews with fishermen who had . The research results show that this can occur due to a lack of public awareness in managing finances and erratic spending every day so that financial management is not well organized. However, there are visible challenges in understanding and implementing financial recording in this sector.